Evaluasi Kinerja Alat Gali Muat dan Alat Angkut Untuk Mencapai Target Produksi Pada Penambangan Batukapur di Area 242 (Tajarang) PT. Semen Padang - Heksali Preduanda; Ansosry Ansosry (Journals Mining Engineering : Bina Tambang, 2019)
This study aimed to calculate the actual productivity of mechanical devices, to get an effort to improve work efficiency to achieve the planned production target, to get the transportation equipment needed to reduce waiting time by using queuing theory calculations in 242 Area limestone mining (Tajarang) PT. Semen Padang. The mining system was done by the quarry method which was of type side hill type with a production target in 2019 of 5,196,699 tons with an average production target of 1,200 tons per hour. The equipment used consists of 1 unit excavator Hitachi EX2500-6 and 5 units of Komatsu HD 785-7 dump truck. The actual productivity of the two devices was able to produce 1,174.85 tons/hour and 975.55 tons/hour respectively. By improving the effective working time, work efficiency could be increased to 86% and made improvements to the composition of the equipment obtained productivity results 1 unit excavator of Hitachi EX2500-6 able to reach the number 1,443.38 tons/hour and 4 units of Komatsu HD dump truck transported 785-7 of 1,362.72 tons/hour. The results of this study mean that the effective time of work and the harmony of work of actual mechanical devices has not been maximized.Keywords:  Productivity, Work Efficiency, Match Factor, Excavator, Dump Truck.